2015
DOI: 10.1097/jto.0000000000000615
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Therapy for Brain Metastases in EGFR-Mutated and ALK-Rearranged Non-Small-Cell Lung Cancer

Abstract: Approximately half of all patients with non-small-cell lung cancer (NSCLC) develop brain metastases (BM) during the course of their disease, leading to significant challenges in treatment. Molecular targeted tyrosine kinase inhibitors have proven effective for patients with activating mutations in the epidermal growth factor receptor gene and chromosomal rearrangements involving the anaplastic lymphoma kinase gene. Despite their efficacy in systemic disease control, their effectiveness in patients with BM is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(47 citation statements)
references
References 93 publications
(83 reference statements)
2
45
0
Order By: Relevance
“…In patients with advanced and metastatic NSCLC, brain metastasis is one of the most common complications. 2,10 Moreover, we found, in our case, that the BBB permeability of crizotinib was poor, in concordance with literature reports, which may result in intracranial disease progression. A retrospective analysis of a large cohort of patients pooled from two clinical trials (PROFILE 1005 and 1007, which involved 275 patients) found that crizotinib was associated with an intracranial disease control rate (DCR) of 56%-62% after 12 weeks of therapy.…”
Section: What Is New and Conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…In patients with advanced and metastatic NSCLC, brain metastasis is one of the most common complications. 2,10 Moreover, we found, in our case, that the BBB permeability of crizotinib was poor, in concordance with literature reports, which may result in intracranial disease progression. A retrospective analysis of a large cohort of patients pooled from two clinical trials (PROFILE 1005 and 1007, which involved 275 patients) found that crizotinib was associated with an intracranial disease control rate (DCR) of 56%-62% after 12 weeks of therapy.…”
Section: What Is New and Conclusionsupporting
confidence: 92%
“…1 Patients with this cancer variant have a dismal prognosis and limited treatment options when it has progressed to intracranial metastasis, because of inadequate drug penetration into the central nervous system (CNS). 2 Factors associated with response to TKI therapy have been reported to include pharmacokinetic and biodynamic resistance phenomena. [3][4][5] For pharmacokinetic resistance, preclinical studies have demonstrated that many drugs are substrates for drug efflux transporters, such as P-glycoprotein (P-gp), that are robustly expressed on the BBB to further reduce intracellular drug levels and limit antitumour activity in the CNS (2).…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…In addition, osimertinib for EGFR T790M-positive lung cancer has shown a benefit in progression-free survival even in patients with brain metastasis [33]. Thus, as some agents are effective in cases of brain metastasis, targeted therapy without RT to the brain is gaining interest, not only for small asymptomatic brain metastases but also for cases of leptomeningeal disease and postoperative brain metastasis [34]. In our study, targeted therapy was a significant beneficial factor for intracranial recurrence compared to no systemic treatment by univariate analysis (p = 0.023) and was a borderline beneficial factor by multivariate analysis (p = 0.058), whereas chemotherapy was not significant when compared to no systemic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, more patients in the targeted therapy group received WBRT (7 of 11) as compared with chemotherapy group (12 of 25) and no systemic treatment (7 of 17) groups. Currently, the role of targeted therapy in the management of brain metastasis from lung cancer has not been clearly established [34]. The question of whether targeted therapy could replace WBRT in the management of brain metastasis, including the role of controlling the microscopic metastasis such as cerebrospinal fluid contamination from surgical resection, remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…As with EGFR-mutated disease, CNS progression is a common complication, with upwards of 45% of patients with CNS involvement by 3 years in the setting of targeted therapy [Rangachari et al 2015]. For further information on management and treatment implications of CNS disease, please refer to these recent reviews [Costa et al 2015;Rangachari et al 2015;Baik et al 2015]. Secondgeneration ALK TKIs with more potent activity against ALK and ALK kinase mutants have been developed and are being studied.…”
Section: Resistance To Alk Blockade In Advanced Nsclc: Second-generatmentioning
confidence: 99%